FRI0348 PERSISTENCE OF SECUKINUMAB AND USTEKINUMAB IN PSORIATIC ARTHRITIS: A REAL-WORLD MULTICENTRIC COHORT OF 409 PATIENTS. (2nd June 2020) - Letarouilly, J. G.; Flachaire, B.; Labadie, C.; Cohen, N.; Kyheng, M.; Sellam, J.; Richette, P.; Dieudé, P.; Claudepierre, P.; Fautrel, B.; Houvenagel, E.; Nguyen, C. D.; et al.
Abstract : Background: Real-world data are missing for Ustekinumab (UST) and secukinumab (SEK) in psoriatic arthritis (PsA). Objectives: To evaluate the characteristics of the patients (pts) with PsA treated by UST or SEK and to assess real world persistence of UST and SEK in PsA. Methods: This is a retrospective, multicenter study of pts with PsA (CASPAR criteria or diagnosis confirmed by a rheumatologist) initiating UST or SEK with a follow-up ≥ 6 months from January 2011 to April 2019. The comparison of persistence between UST and SEK was analysed using a Cox model with an inverse probability of treatment weighting propensity score including 11 confounding factors. Subgroup analyses (age>65 years, gender, Body Mass Index (BMI), Charlson score>2, psoriasis, CRP>5mg/L, number (nb) of prior biotherapies, proportion of pts on maximum dose of UST or SEK, combination with methotrexate (MTX), enthesitic and axial forms of PsA) were also performed to test the heterogeneity of UST and SEK persistence. Finally, 2 sensitivity analyses were performed, first excluding the pts treated before the marketing authorization of SEK, and then excluding the pts that underwent a molecule switch. Causes of discontinuation were also collected. Results: 406 pts were included: 245 with UST and 161 with SEK. At baseline before propensity score-matching, the UST group has a higher BMI (28.9 ± 6.4 kg/m 2 vs. 27.4 ± 6.0 kg/m 2 ), more peripheral forms (98% vs. 90.8%), a higher nb of active smokers (27.1% vs. 19.9%), a higher frequency of psoriasis (96.3% vs. 83.2%), less MTX users (38.9% vs. 44.2%), a higher nb of pts with CRP >5mg/L (54.3% vs. 47%), a higher nb of pts naïve to biotherapies (22% vs. 13%) and a higher nb of pts with recommended dosing (97.3% vs 50.9%). The median persistence was 9.4 months and 14.7 months for UST and SEK, respectively. The persistence rate was lower in the UST group compared to the SEK group (40.9% vs. 59.1% % at 1 year; 26.4% vs. 38.0% at 2 years; weighted HR=1.42; 95% CI 1.07 to 1.92; p=0.015) (Fig 1 ). In subgroup analysis, combination with MTX was associated with a higher persistence rate in the patients with SEK compared to those receiving UST: 43.6% vs. 23.2% (HR=2.20; 95% CI 1.30 to 3.51; p=0.001), whereas no difference was observed in SEK and UST monotherapy: 33.8% vs 28.4%, respectively (HR=1.06; 95% CI 0.74 to 1.53; p=0.75) (Fig 2 ). A similar difference was found in the sensitivity analyses, with however a difference at the limit of significance for the analysis excluding pts with a molecule switch (adjusted HR=1.35; IC95% 0.96 to 1.92; p=0.085). The causes of discontinuation were due to inefficacy in 85% of cases and an adverse event in 12% of cases (19% in the SEK group and 9% in the UST group). Conclusion: In this first real-world study comparing UST and SEK persistence in PsA, the persistence of SEK was longer than that of UST. Subgroup analysis revealed this difference of persistence was restricted to patients treated in combination with MTX. Disclosure of Interests: Jean-Guillaume Letarouilly Grant/research support from: Research grant from Pfizer, Benoît Flachaire: None declared, Céline Labadie: None declared, Nicolas Cohen Speakers bureau: Novartis, Janssen, Maeva Kyheng: None declared, Jérémie SELLAM: None declared, Pascal Richette: None declared, Philippe Dieudé: None declared, Pascal Claudepierre Speakers bureau: Janssen, Novartis, Lilly, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, Eric Houvenagel Speakers bureau: Janssen, Novartis, Chi Duc Nguyen: None declared, Marie-Hélène Guyot: None declared, Nicolas Segaud: None declared, Frederic Maury: None declared, Laurent Marguerie: None declared, Xavier Deprez Speakers bureau: Novartis, Janssen, Jean-Hugues Salmon Speakers bureau: Novartis, Janssen, Guy Baudens: None declared, Corinne Miceli Richard: None declared, Elisabeth Gervais Speakers bureau: Novartis, Janssen, Roche, Pfizer, BMS, Abbvie, Isabelle CHARY VALCKENAERE: None declared, Pierre Lafforgue Speakers bureau: Novartis, Janssen, Damien LOEUILLE: None declared, Christophe Richez Consultant of: Abbvie, Amgen, Mylan, Pfizer, Sandoz and UCB., Thao Pham Speakers bureau: Novartis, Janssen, Lilly, Rene-Marc Flipo Speakers bureau: Novartis, Janssen, Lilly